Dinamika Integrasi Lokal Warga Eks Timor Timur di Wilayah Pemukiman Pengungsi Kabupaten Kupang Provinsi Nusa Tenggara Timur - Skolastika Genapang Maing; Sidik Jatmika (Universitas Diponegoro, 2021)
This article examines the dynamics of the method local integration of ex-East Timorese residents in the refugee settlement area of Kupang Regency, East Nusa Tenggara Province.The author uses the Functional Theory by Talcott Parsons and the Local Integration concept by UNHCR as set out in Refugee Convention 1951. While related to research method, the author uses qualitative methods with descriptive approaches and secondary data. The results showed that the implementation of local integration of ex-East Timorese was not as expected. This is due to obstacles in every level of the local integration process, both related to legality, economy and socio-culture. Social harmony between local residents and ex-refugees isn’t always become the commitment of the central and regional governments, but requires the role of the informal sector, especially local communities at refugee settlement areas. The process of local integration that is not going well can lead to social conflict in the community.